2022
DOI: 10.18421/tem112-23
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Digital Banking Adoption During Post-Coronavirus Pandemic: An Integration of Technology Readiness and Technology Acceptance Model

Abstract: Digital banking can make banking transactions easier in daily life. However, the presence of technology does not seem to be welcomed. This is due to the unpreparedness of technology for digital banking technology. The target respondents are millennial generation users in Indonesia who use digital banking services during post-corona virus. The sample selection using random sampling with 422 respondents. The data analyses were performed using SEM-PLS. The results show that Optimism, Discomfort, and Insecurity af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…This study showcased that positive factor of technological readiness such as optimism and innovativeness, along with negative factors like discomfort, can act as significant antecedents within the TAM mode. This aligns with the findings of the study by Musyaffi et al (2022), which investigated digital banking adoption in the post-COVID-19 pandemic era, providing similar evidence. However, while the study by Musyaffi et al (2022) emphasized innovativeness as the most crucial factor, this current study revealed that optimism plays the most significant role in technology adoption.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…This study showcased that positive factor of technological readiness such as optimism and innovativeness, along with negative factors like discomfort, can act as significant antecedents within the TAM mode. This aligns with the findings of the study by Musyaffi et al (2022), which investigated digital banking adoption in the post-COVID-19 pandemic era, providing similar evidence. However, while the study by Musyaffi et al (2022) emphasized innovativeness as the most crucial factor, this current study revealed that optimism plays the most significant role in technology adoption.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…The next procedure after R-square is to test the effect size (f2) to determine the size of the effect of each exogenous variable on the model. There are three types of influence, namely small (0.02), medium (0.15), and large (0.35) (Hair, Risher, Sarstedt, & Ringle, 2019;Musyaffi et al, 2022). Table 7 shows that the variable of DFL has a large effect on FB; it is 0.651.…”
Section: Assessment Of Modelmentioning
confidence: 99%
“…Meanwhile, FC has a medium effect on FB (0.206) and indirectly affects FW on a large scale (0.453). (Musyaffi et al, 2022;Saptono et al, 2021). The model has predictive relevance if the value of Q2 is more than 0 (zero).…”
Section: Assessment Of Modelmentioning
confidence: 99%
“…Meanwhile, insecurity and discomfort act as inhibitors that can prevent someone from using new technology [26], [27]. High technological readiness can affect a person's perception of the ease and usefulness of viewing technology [28]. Insecurity for technology users occurs because there is no guarantee for the products and services of the technology [17].…”
Section: Tri Analysismentioning
confidence: 99%